Aneuploidy Screening for Embryo Selection - Fragouli, Elpida; Wells, Dagan (Seminars in Reproductive Medicine, 2012)
Chromosome abnormalities are extremely common in human oocytes and embryos and are associated with a variety of negative outcomes for both natural cycles and those using assisted conception techniques. Embryos containing the wrong number of chromosomes (aneuploidy) may fail to implant in the uterus, miscarry, or lead to children with serious medical problems (e.g., Down syndrome). Preimplantation genetic screening (PGS) is a method that seeks to improve the outcomes of assisted reproductive treatments, such as in vitro fertilization (IVF), by ensuring that the embryos chosen for transfer to the uterus are chromosomally normal. Here we summarize published and novel data concerning the frequency and variety of chromosomal abnormalities seen in oocytes and embryos at the cleavage and blastocyst stages of development. Clinical outcomes of studies using PGS are presented, and the controversy over the use of chromosome screening as a tool for embryo selection is discussed. We describe validation and preliminary clinical data from the new generation of methods being used for PGS, including comparative genomic hybridization (CGH), microarrays (aCGH and single nucleotide polymorphism arrays), and quantitative polymerase chain reaction. These methodologies allow comprehensive chromosomal analysis, provide high accuracy, and have yielded encouraging preliminary clinical data. The combination of advances in genetics and embryology seems poised to usher in a new era in the treatment of infertility.
Keywords: preimplantation genetic screening; embryo; oocyte; FISH; aCGH